KANDUNGAN N, P, K DAN Pb KOMPOS LIMBAH KERTAS BERTINTA DAN SAYURAN DENGAN AKTIVASI CAIRAN RUMEN - Hesti Kurniahu; Sriwulan Sriwulan; Annisa Rahmawati; Riska Andriani (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2022)
The compost of inked paper and vegetable waste mixture is a result of the process of degradation of the components of lignin and cellulose. The process was activated by cellulolytic bacteria from rumen liquor. The aim of this study to know the compost quality of the inked paper and vegetable waste mixture. The content of by-products of compost studied were the levels of N, P, K, and Pb heavy metals. The composting process in this study was carried out by anaerobic. The N test used the Kjeldahl method, the P and K test used the Bray 1 method, and the Pb test used the AAS method (Atomic Adsorption Spectrophotometer). The data were analyzed using Manova statistical tests with LSD post hoc tests. From the observations, it was known that the addition of rumen liquor had a significant effect on the levels of P with the most optimal concentration of 50%, while for N and K levels and Pb heavy metals content was not significantly different. However, the average level of nutrient elements N (0.87% to 1.1%), P (0.2% to 0.5%) and K (0.52% to 0.58%) and Pb heavy metals (0.61ppm to 4.09 ppm) fulfill SNI 19-7030- 2004 standard.